Prognostic value of lymph node ratio in patients with non-small cell lung cancer: a systematic review and meta-analysis - Zheng, Junhuang; Zhong, Haoyu; Quan, Enxiang; Gao, Zhiyan; Ying, Songsong (Frontiers in Oncology, 2025)
Background and purposeThe lymph node ratio (LNR), by indirectly quantifying the dynamic balance between metastatic burden and host immune clearance, may provide more accurate prognostic stratification information. This meta-analysis aims to evaluate the prognostic value of LNR in patients with non-small cell lung cancer (NSCLC).MethodsA systematic literature search was conducted in PubMed, Embase, Cochrane, and Web of Science databases, with the search date up to January 7, 2025. Studies were strictly selected based on pre-specified inclusion and exclusion criteria. Data were merged and analyzed using Stata 16.0.ResultsThis meta-analysis included 11 studies. High LNR was significantly associated with decreased overall survival (OS) (multivariable HR=1.76, 95% CI=1.36-2.27; univariable HR=2.26, 95% CI=1.95-2.63) and increased risk of shorter disease-free survival (DFS) (multivariable HR=1.66, 95% CI=1.48-1.88). Subgroup analysis showed that regardless of whether the LNR cutoff was set at >0.25 (OS-HR=1.62; DFS-HR=1.82) or ≤0.25 (OS-HR=2.02; DFS-HR=1.58), high LNR indicated poor prognosis. Heterogeneity analysis showed high heterogeneity for OS outcomes (I²=91.8%) and low heterogeneity for DFS outcomes (I²=21.5%). After publication bias was corrected by trim-and-fill method, the combined effect size remained stable.ConclusionLNR is an independent prognostic factor for survival in NSCLC patients. Future prospective studies are needed to optimize the LNR cutoff values and integrate molecular biomarkers to construct precise prognostic models, which could provide evidence for updating the TNM staging system and personalized treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251022895, identifier (CRD420251022895).